Notes on Schubert, Grothendieck and Key Polynomials - Kirillov, A.N. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We introduce common generalization of (double) Schubert, Grothendieck, Demazure, dual and stable Grothendieck polynomials, and Di Francesco-Zinn-Justin polynomials. Our approach is based on the study of algebraic and combinatorial properties of the reduced rectangular plactic algebra and associated Cauchy kernels.